Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Höhe} \qquad c \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)}\\ \textbf{Gegeben:} \\ c=8m \qquad a=3m \qquad O=4m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)} \\ c=8m\\ a=3m\\ O=4m^{2}\\ b = \frac{4m^{2}-2\cdot 3m\cdot 8m}{2\cdot (3m+8m)}\\\\b=-2m \\\\\\ \tiny \begin{array}{|l|} \hline c=\\ \hline 8 m \\ \hline 80 dm \\ \hline 800 cm \\ \hline 8\cdot 10^{3} mm \\ \hline 8\cdot 10^{6} \mu m \\ \hline 0,008 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline a=\\ \hline 3 m \\ \hline 30 dm \\ \hline 300 cm \\ \hline 3\cdot 10^{3} mm \\ \hline 3\cdot 10^{6} \mu m \\ \hline 0,003 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline O=\\ \hline 4 m^2 \\ \hline 400 dm^2 \\ \hline 4\cdot 10^{4} cm^2 \\ \hline 4\cdot 10^{6} mm^2 \\ \hline 0,04 a \\ \hline 0,0004 ha \\ \hline 4\cdot 10^{-6} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline b=\\ \hline -2 m \\ \hline -20 dm \\ \hline -200 cm \\ \hline -2\cdot 10^{3} mm \\ \hline -2\cdot 10^{6} \mu m \\ \hline -0,002 km \\ \hline \end{array}$